Dakwah di Media Digital Sebuah Analisis Representasi Nilai-Nilai Islam Pada Film Merindu Cahaya De Amstel: Da'wah in Digital Media: An Analysis of the Representation of Islamic Values ​​in the Film Merindu Cahaya De Amstel - Hamandia, Muhammad Randicha; Hertimi, Sri; Umariani, Afriyanti (KIRANA : Social Science Journal, 2025)
Film is one of the most effective media for preaching in conveying moral and religious messages, including in the context of Islamic preaching. In this case, film acts as a means of communication that can reach a wider audience. One interesting example is the film "Merindu Cahaya de Amstel," which combines a love story with Islamic values ​​conveyed through narratives and characters that are relevant to everyday life. This study aims to identify the preaching messages contained in the film "Merindu Cahaya de Amstel" using Roland Barthes' semiotic analysis. In this analysis, we will explore messages related to Islamic values ​​contained in the film. This study refers to Roland Barthes' semiotic analysis theory, which includes three meanings: connotation, denotation, and myth. The method used in this study is a qualitative approach, where secondary data is collected to analyze the existing preaching messages. The results of the study show that each scene and dialogue between characters contains these three meanings, namely connotation, denotation, and myth. In this analysis, the dialogue is processed through metaphors and implied meanings, so that the real meaning can be produced. In addition, in the representation of Islamic values ​​messages, there are three important categories: messages of faith, sharia, and morals. This research is expected to help the public in choosing films that convey positive messages. In addition, films that contain preaching messages also have the potential to provide a positive impact on the lives of their viewers.